What are you looking for? An eye-tracking study of information usage in web search - Cutrell, Edward; Guan, Zhiwei; Cutrell, Ed (CHI '07: Proceedings of the SIGCHI conference on Human factors in computing systems, 2007)
Web search services are among the most heavily used applications on the World Wide Web. Perhaps because search is used in such a huge variety of tasks and contexts, the user interface must strike a careful balance to meet all user needs. We describe a study that used eye tracking methodologies to explore the effects of changes in the presentation of search results. We found that adding information to the contextual snippet significantly improved performance for informational tasks but degraded performance for navigational tasks. We discuss possible reasons for this difference and the design implications for better presentation of search results.
Best of CHI honorable mention